WEB-ТЕХНОЛОГИЯЛАР АСОСИДА БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ КАСБИЙ ТАЙЁРГАРЛИГИНИ ТАКОМИЛЛАШТИРИШНИНГ ДИДАКТИК ИМКОНИЯТЛАРИ - Мамбетниязов, М.Т. (SCIENCE and SOCIETY, 2022)
The didactic possibilities of improving the professional training of future teachers based on Web-technologies and the issue of studying the problems in this regard are reflected in the article.
Keywords: modern education system; didactic opportunities; professional training; future teachers; Internet; Web-technologies; computer and information